Strange Tangents - Matt Hutchison (Oz, 2017)
At a moment in time when designers, architects and makers have an unprecedented selection of high-precision machines, computational tools, and networks of information at their disposal, the term “craft” seems anachronistic and yet still somehow overused. Once synonymous with dexterous coordination between the hand and mind of the maker and grounded in the physical world, the term has been appropriated and misused for any number of pursuits. A reconsideration of “craft” is in order, as it is situated within contemporary design (and making) practices.